Analisis Dampak Pembangunan Infrastruktur Terhadap Lingkungan - Kevin Berkat Mendrofa; Agus Rahmat Ndruru; Desman Telaumbanua; Muhammad Haris Zalukhu (CV. SINAR HOWUHOWU, 2026)
Infrastructure development plays a crucial role in promoting economic growth and improving community welfare, particularly in island regions such as Nias. However, such development activities also have the potential to generate negative environmental impacts. This study aims to analyze the environmental impacts of infrastructure development in Nias and to identify possible mitigation efforts. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that infrastructure development provides positive impacts, including improved accessibility, regional connectivity, and local economic growth. Nevertheless, negative impacts were also identified, such as soil erosion, water pollution due to sedimentation, air quality degradation, and loss of biodiversity. These impacts occur during both the construction and operational phases. Therefore, the implementation of sustainable development principles is essential through environmental impact assessment (EIA), proper waste management, and strict supervision to minimize adverse effects. This study is expected to serve as a reference for formulating environmentally sustainable infrastructure development policies, especially in island regions.